Relações entre localização geográfica, perfil sócio-econômico e as condições higiênico-sanitárias dos açougues no município de Belo Horizonte/MG - Denise Toledo de Paula (2006)
The objective of this paper is to profile the cleanliness..ie- Hygiene and Sanitation- of Butcher Shops/Meat Markets in Municipal Belo Horizonte-MG, by way of routine inspections utilized by the Sanitation Department. The Meat Market/Butcher Shops were classified not only by their regional administrative parameters but by their Socio-Economic Class whose results were individualized for each of those parameters. 212 Meat Markets/Butcher Shops were analyzed out of the 1059 registered with the Sanitation Department analyzing the results of the the routine inspections and subsequent points given, each butcher shop recieved a Certificate of Cleanliness ranging from Bad to Excellent. Utilizing the data collected from the inspections, the Main Characteristics and thus, deficiencies, were found for each of the 9 Administrative Regions and the 6 Socio-economic classes determined for the region. This information becomes and important factor for future inspections directed by the Sanitation Department. It was noted that the majority of the certificates of cleanliness administrated were in the range of Regular to Good which demonstrated the neccesity of stricter actions from the Sanitation Dept. in all the Butcher Shop and Meat Markets in the Region. It was also noted that there must be an investment increase in the Municipal Sanitation Dept., mainly in the Human Resources Dept., thus establishing the continual capacitation of Veterinarians and inspectors and the importance of divulging Educative Campaigns for the general population in this way creating a sort of Sanitary conciousness enabling each citizen to become their own Health Inspector.